Capsisteroids A–F, withanolides from the leaves of Solanum capsicoides. Issue 108 (19th October 2015) - Chen, Bo-Wei; Chen, Yang-Yih; Lin, You-Cheng; Huang, Chiung-Yao; Uvarani, Chokkalingam; Hwang, Tsong-Long; Chiang, Michael Y.; Liu, Ho-Yih; Sheu, Jyh-Horng
Abstract : A known withanolide steroid cilistol G (1 ) and six new withanolides, capsisteroids A–F (2–7 ), were isolated from the EtOAc extract of the leaves of Solanum capsicoides . Abstract : A known withanolide steroid cilistol G (1 ) and six new withanolides, capsisteroids A–F (2–7 ), were isolated from the EtOAc extract of the leaves of Solanum capsicoides . The structures of compounds1–7 were elucidated by extensive spectroscopic analysis, including 2D NMR spectroscopy (COSY, HSQC, HMBC, and NOESY). The structure of1 was further confirmed by a single-crystal X-ray diffraction analysis. These compounds were found not to be cytotoxic toward a limited panel of cancer cell lines. Further, the anti-inflammatory activity of compounds1–7 was studied by measuring their ability to suppress superoxide anion generation and elastase release in fMLP/CB-induced human neutrophils.